Canopy Cover Temperature & Drought Tolerance Indices in Durum Wheat (Triticum durum Desf.) Genotypes under Semi-arid Condition in Algeria - Guendouz, Ali; Frih, Benalia; Oulmi, Abdelmalek (International Journal of Bio-resource and Stress Management, 2021)
This experiment was carried out at Setif Agricultural Experimental Station in Algeria during 2017–2018 crop season using five cultivars (Triticum durum Desf.) to determine differences in the relationship between (CT and drought resistance indices values based on their difference in yielding under irrigated and non-irrigated conditions and sown in a random block design with three replications. Our study aim to determine differences in the relationship between CT and drought resistance indices values and grain yield GY under both conditions to evaluate the effect of canopy temperature in drought tolerance of durum wheat. Five durum wheat (Triticum durum Desf.) genotypes were studied based on their difference in yielding under irrigated and non-irrigated conditions in conception of a random block design with three replications. The following measurements were applied: GY, CT canopy cover temperature depression CTD and seven drought tolerance indices (HM-SSI-GMP-STI-YSI-MP-TOL). ANOVA showed that genotype effect and irrigation regime effect were highly and significantly on CT and CTD under both stressed (s) and watered (i) conditions. The interaction Genotype×irrigation regime was significant for CT and CTD. PCA showed that CTDs was related with HM, GMP, STI, and MP in indication of drought tolerance, where CTDi was related with TOL and SSI in indication of drought sensitivity. A negative correlation showed between CT and CTD, higher values of CT compared to environmental temperature implies negative values of CTD which indicates drought sensitivity; on the other hand, CT values lower than environmental temperature implies positive CTD values indicating drought tolerance.